Analytical Essay on Creativity, Thinking Skills, and Innovation in Environmental Education in Schools - Yunitta, Sri; Kamaludin, Faisal Sundani (Journal of Applied Business, Taxation and Economics Research, 2026)
Environmental education plays a strategic role in shaping a generation that has awareness, creativity, thinking skills, and the ability to innovate in facing global environmental challenges. This article aims to critically analyze the role of creativity, thinking skills, and innovation in environmental education in schools and identify challenges and opportunities in its implementation. This study uses a qualitative approach with analytical methods on various relevant literature reviews and empirical findings. Data were obtained through analysis of scientific journals, research reports, and education policy documents related to environmental education and 21st-century learning. The results of the analysis show that the integration of creativity, critical thinking skills, and innovation in environmental education can improve students' conceptual understanding, environmental awareness, and their ability to formulate solutions to environmental problems in a contextual manner. However, implementation in schools still faces obstacles in the form of limited teacher competence, a curriculum that does not fully support innovative learning, and a lack of institutional support. Therefore, systematic efforts are needed through strengthening teacher capacity, developing an adaptive curriculum, and supporting school policies so that environmental education can function optimally in shaping students who are creative, critical, and oriented towards sustainability.